Influenza A H5N1 and HIV co-infection: case report - Fox, A; Horby, P; Ha, N; Hoa, L; Lam, N; Simmons, C; Farrar, J; Van Kinh, N; Wertheim, H (BioMed Central, 2010)
BACKGROUND: The role of adaptive immunity in severe influenza is poorly understood. The occurrence of influenza A/H5N1 in a patient with HIV provided a rare opportunity to investigate this. CASE PRESENTATION: A 30-year-old male was admitted on day 4 of influenza-like-illness with tachycardia, tachypnea, hypoxemia and bilateral pulmonary infiltrates. Influenza A/H5N1 and HIV tests were positive and the patient was treated with Oseltamivir and broad-spectrum antibiotics. Initially his condition improved coinciding with virus clearance by day 6. He clinically deteriorated as of day 10 with fever recrudescence and increasing neutrophil counts and died on day 16. His admission CD4 count was 100/microl and decreased until virus was cleared. CD8 T cells shifted to a CD27+CD28- phenotype. Plasma chemokine and cytokine levels were similar to those found previously in fatal H5N1. CONCLUSIONS: The course of H5N1 infection was not notably different from other cases. Virus was cleared despite profound CD4 T cell depletion and aberrant CD8 T cell activation but this may have increased susceptibility to a fatal secondary infection.